PInk salmon Oncorhynchus gorbuscha (Salmoniformes, Salmonidae) on the continental coast of the Okhotsk Sea. Communication 1. The juveniles - S. L. Marchenko (Известия ТИНРО)
Data on juvenile pink salmon from the continental coast of the Okhotsk Sea obtained in 1960s–2010s are summarized. The timing and dynamics of their downstream migration are considered in terms of biological parameters and nutrition. Brief information on their early marine life is presented. The mass seaward migration of pink salmon begins when the river water is warmed to 2.5–4.0 оC. The juveniles migrate from rivers to the coastal marine waters diurnally. During the seaward migration, their body length and weight do not change significantly, as a rule, but a portion of fish with external feeding increases. Year-toyearly, in the rivers the portion of juveniles switched to external feeding is higher in the years with mild spring flood.